Digital Borrowing Behavior Among Students: The Role of Financial Literacy, Lifestyle, and Financial Inclusion in Online Loan Use - Nur Istiqomah; Sutrisno Sutrisno (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of financial literacy, lifestyle, and financial behavior on the use of online loans, with financial inclusion as a moderating variable among university students in Yogyakarta. The increasing use of online lending services among students reflects challenges in personal financial management amid the convenience of financial technology (fintech). This research employed a quantitative approach using a survey method, with questionnaires distributed to 170 student respondents who had previously used online lending services. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method. The results indicate that financial literacy does not have a significant effect on the decision to use online loans, while lifestyle and financial behavior have a positive and significant influence on online loan usage. Moreover, financial inclusion moderates the relationship between financial behavior and online loans, but does not moderate the relationship between financial literacy or lifestyle and online loans. These findings suggest that improving financial literacy alone is insufficient to reduce online loan usage without fostering prudent financial behavior and controlling consumptive lifestyles. This research contributes to the development of financial education policies and strategies to enhance sustainable financial inclusion within higher education institutions.